Adaptasi Komunikasi Internal Berbasis Nilai Islam pada Organisasi Nirlaba di Era Kerja Hibrida: Sebuah Tinjauan Literatur Integratif - Syukri, Sarah; Tarigan, Muhammad Iqbal Suranta (Universitas Islam Negeri Raden Intan Lampung, 2026)
The post-pandemic adoption of hybrid work models presents a paradoxical challenge for Islamic faith-based non-profit organizations: increased digital connectivity coincides with the erosion of social cohesion and employee emotional attachment. This study aims to construct a communication adaptation strategy framework capable of bridging technological efficiency with the preservation of organizational spiritual values. Using an Integrative Literature Review method, this study synthesizes theoretical and empirical literature published between 2019 and 2025. The analysis reveals that the lack of non-verbal cues in computer-mediated communication triggers